Analysis and Control of Offshore Wind Power Collection Systems - Fan, Yuanyuan (Curtin University, 2016)
The utilization of offshore wind energy in power systems generally includes power generation, power collection and power transmission. An efficient wind energy conversion system is proposed for offshore wind power generation. Three types of DC collection systems are discussed for both normal and fault operations. To integrate the power from several offshore wind farms with a grid, the multi-terminal HVDC system is applied. All the proposals are verified through extensive simulation studies.